Managing and responding to the crisis of sexual harassment at the University of Argopuro - Wulandari, Maulina Pia; Layna, Nadia Luitsa (PRofesi Humas, 2025)
Background: Sexual harassment incidents at higher education institutions can trigger crises that have a detrimental impact on public trust and institutional reputation. Purpose: This study analyzes the crisis management and reaction approach employed by the University of Argopuro in the aftermath of a sexual harassment event involving its Rector. Methods: The study employed a qualitative case study approach and collected data through in-depth interviews with senior administrators and document analysis. Results: The findings reveal that the university implemented a five-step crisis management model, integrating adaptive strategies with Image Restoration Theory (IRT) and Situational Crisis Communication Theory (SCCT). These strategies focused on transparency, accountability, and victim protection. The study highlights those key methods, including appointing a spokesperson, issuing press releases, forming a crisis management team, and establishing a Gender Studies Centre to foster systemic reform and prevention. The study offers four novel crisis response strategies: attitude statements for transparency, victim protection plans, organizational accountability mechanisms, and follow-up initiatives to sustain cultural transformation. While SCCT and IRT provided a foundational framework, this study highlights the limitations of the frameworks in addressing the deeper systemic issues surrounding sexual harassment, emphasizing the need for long-term cultural change. Moreover, the results highlight the need to integrate crisis communication theories with adaptive, victim-centered approaches to address preventable crises effectively. Conclusions: The study concludes that a comprehensive and transparent crisis management process can mitigate reputational damage, restore stakeholder trust, and promote systemic reforms.  Implications: The study contributes to public relations literature by establishing the applicability of combined theoretical and adaptive strategies in complex academic crises, recommending practical insights for public relations practitioners in higher education institutions worldwide. Future research should expand the application of these strategies across diverse cultural and organizational contexts to validate their effectiveness.